The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.2.20783/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Scientometric Analysis of Neuroblastoma Research

Abstract: Background: There are thousands of research articles in the field of neuroblastoma that have been published over the past few decades. However, the heterogeneity and variable quality of scholarly data may challenge scientists or clinicians to survey all published articles. However, holistic measuring and analyzing of neuroblastoma related literature by sophisticated mathematical methods can provide a unique opportunity to gain deep insights into the global research performance and collaborative architectonical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Finally, we retrieved the metadata for these 4,488 articles which included author names, titles, country of corresponding author, total number of publications, citation counts (i.e., total citations, average article citations, and number of citing articles with and without selfcitations), journal sources, keywords, countries and regions, and author-level metrics (c.f., Martynov et al, 2020).…”
Section: Methods and Datamentioning
confidence: 99%
“…Finally, we retrieved the metadata for these 4,488 articles which included author names, titles, country of corresponding author, total number of publications, citation counts (i.e., total citations, average article citations, and number of citing articles with and without selfcitations), journal sources, keywords, countries and regions, and author-level metrics (c.f., Martynov et al, 2020).…”
Section: Methods and Datamentioning
confidence: 99%
“…As a tool widely used for qualitative and quantitative analysis of global scientific literature, bibliometric analysis can effectively show the knowledge structure and possible development trend of specific fields through information visualization [16][17][18]. Bibliometric analysis has been performed in the research field of nervous system diseases [19,20]. However, the specific mechanism of autophagy in ischemic stroke is still unknown [21], and the role of autophagy in ischemic stroke cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, it was estimated that 4% of the world's research output was devoted to the coronavirus in 2020, but 2020 also observed an exponential increase in publications on all subjects submitted to scientific journals, perhaps many researchers had to stay at home and focus on writing up papers rather than conducting science [ [17] , [18] , [19] ]. Bibliometric studies provide interesting methods for measuring the scientific value of a particular field over a specific time [ [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
“…The known increase in COVID-19 pandemic research productivity worldwide, requires attention to bibliometric analysis of the local publication patterns to shed light on where we stand. Bibliometric studies or scientometric assessment has been utilized to assess the scientific output of different world regions in several scientific fields [ [12] , [13] , [14] ]. Noteworthy, GCC countries bibliometric indicators suggested general paucity in productivity and reduced visibility compared to other countries [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%